Language Orientations of Chilean Secondary Students in Relation to the Study of English as a Foreign Language - Barger, Corinne; Sandoval Rubilar, Pedro (Colombian Applied Linguistics Journal, 2020)
Why teach English in Chile? Dominant public discourse claims for economic development, but with limited social mobility, do students from differing socio-economic groups perceive the same need? Recognising the influence of student belief systems on language acquisition, clashing language orientations could be creating unfavourable classroom environments. Thus, this study set out to identify the language orientations that secondary students recognise and hold in relation to the study of English with the purpose of helping English as foreign language (EFL) teachers become aware of the plurality of student perceptions. This was a qualitative multiple-case study which utilised a card-sorting technique paired with hierarchical cluster analysis and multidimensional scaling (MDS) to identify the language orientations and their constructs and semi-structured interviews and classroom observations for verification. Whilst the language orientations students recognise and hold were found to be similar across socio-economic lines, an important issue is the divergence identified between the language orientations associated with the classroom and those that represent student interests, which could be explained due to the lack of intentional and conscious dialogue about the purpose of the classroom curriculum. Vision planning is proposed as a tool for teachers to address this breach between students and classroom curriculum.